The Lost Girls of Paris - Jenoff, Pam (Toronto, Ontario, Canada : Park Row Books, 2019)
"A ... story of friendship and courage centered around three women and a ring of female secret agents during World War II"--
Keywords: World War, 1939-1945 -- Women; Fiction; World War, 1939-1945 -- Underground movements; Fiction; World War, 1939-1945 -- Fiction; Lost articles -- Fiction; Women spies -- Fiction; Manhattan (New York, N.Y.) -- Fiction; Historical fiction; Spy fiction